Research on rating behaviors of bidding evaluation experts in construction projects based on novel integrated methods about reliability and decision entropy - Xiaoping Bai; Meng Jia (Humanities & Social Sciences Communications)
Abstract In recent years, with the rapid development of information technology and the demand for prevention and control of COVID-19, electronic bidding has become very popular, and remote construction project bid evaluation has been widely used. In practice, it is easy to detect and give early warning for propensity abnormal scores with large deviation values. Still, it is impossible to make timely judgments for non-pendency abnormal scores, so its reliability needs to be analyzed. This paper studied the rating behaviors of bidding evaluation experts in construction projects, and proposed novel integrated methods about reliability and decision entropy. Firstly the paper used the power method in numerical algebra to obtain the score closest to the real score of the project and then calculated the decision entropy of the individual expert, and the calculated entropy value corresponds to the reliability of the decision. Finally, the paper determined the warning threshold through instance analysis to monitor the reliability of evaluation expert scoring behaviors. The detailed methods and steps proposed in this paper are helpful in improving the management level of construction project bid evaluation.